On a new algorithm for computing GCD of integer numbers - ST Ishmukhametov; BG Mubarakov; RG Rubtsova; Al Khalidi Arkan Mohammed (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
In the paper we give an introduction to a new algorithm counting the greatest common divisor (GCD) of natural integers called the approximating GCD algorithm introduced by S.Ishmukhametov in 2016. We compare it with the classical Euclidean GCD algorithm and the kary GCD algorithm in spirit of J. Sorenson and K. Weber and outline their advantages and disadvantages.